Launch of the national no-go planting programme Measures and provisions for the crop year - Moussadek, Rachid (2023)
As Morocco is increasingly confronted with the water deficit caused by structural drought, the adoption and deployment of adaptation approaches combining cultural techniques and practices to better value the drop of water, is an essential orientation of the Green Generation strategy. In this sense, direct sowing of cereals is one of the technological packages that has shown its effectiveness in arid and semi-arid areas. Indeed, direct sowing is a method of setting up cereals without any tillage of soil preparation before sowing. Practiced by specific seeders, the technique ensures the maintenance of soil fertility and the conservation of soil moisture. It assumes a reasoning of crop rotation. The promotion of this technology is based on the results of the research carried out. It improves soil fertility and organic matter levels, improves cereal yields by 30% on average and stabilizes them especially in dry years, reduces cereal installation costs by 60% and sowing rates by 30% and reduces soil erosion by more than 50%. It aims to improve agriculture's resilience and adaptation to climate change